Hubungan Self-Efficacy dengan Prokrastinasi Akademik Siswa SMP - Pratama, Mesa Aliata; Dianto, Mori; Triyono, Triyono (Jurnal Bimbingan dan Konseling Ar-Rahman, 2025)
This study aims to investigate the relationship between self-efficacy and academic procrastination among junior high school students. The research method used is a correlational design with a sample of 8th-grade students selected using simple random sampling. Data were collected using self-efficacy scales and academic procrastination scales with a Likert scale type. Statistical analysis was performed using Pearson correlation analysis to examine the relationship between the two variables. The results showed a significant negative relationship between self-efficacy and academic procrastination among junior high school students, with r = -0.536 and p < 0.001. This means that the higher the students' self-efficacy, the lower their academic procrastination. The findings suggest that self-efficacy is a crucial factor influencing academic procrastination among junior high school students. Therefore, teachers and counselors can utilize the results of this study to develop appropriate intervention strategies to enhance students' self-efficacy and reduce academic procrastination. Consequently, this study contributes to the development of more effective educational programs to improve academic achievement among junior high school students. ___________________________________________________________Penelitian ini bertujuan untuk mengetahui hubungan efikasi diri dengan prokrastinasi akademik siswa SMP. Metode penelitian yang digunakan adalah desain korelasional dengan sampel siswa kelas VIII yang dipilih menggunakan teknik simpel random sampling. Data dikumpulkan menggunakan skala efikasi diri dan skala prokrastinasi akademik dengan jenis skala likert. Analisis statistik yang digunakan yang digunakan untuk mengolah hasil penelitian adalah dengan analisis korelasi person untuk mengetahui hubungan antara kedua variabel. Hasil penelitian menunjukan terdapat hubungan negatif yang signifikan antara efikasi diri dengan prokrastinasi akademik siswa SMP yaitu r hitung = -0,536, p= <0.001. Artinya, semakin tinggi efikasi diri siswa, semakin rendah prokrastinasi akademik siswa. Hasil ini menunjukan bahwa efikasi diri merupakan faktor yang penting dalam mempengaruhi prokrastinasi akademik siswa SMP. Oleh karena itu, guru dan konselor dapat menggunakan hasil penelitian ini untuk mengembangkan strategi intervensi yang tepat untuk meningkatkan efikasi diri siswa dan mengurangi prokrastinasi akademik siswa. Dengan demikian, penelitian ini dapat memberikan kontribusi pada pengembangan prokgram pendidikan yang lebih efektif dalam meningkatkan prestasi akademik siswa SMP.